Sistem Pakar Deteksi Dini Kesehatan Mental Menggunakan Metode Dempster-Shafer - Annisa Rahmadhani; Fauziah Fauziah; Andri Aningsih (STMIK PONTIANAK, 2020)
Mental health is an important aspect that needs attention as much as physical health. Lack of public awareness of mental health and the deficiency time and money become some of the thought for someone to be reluctant to check himself with a psychologist / expert. This study aims to do an initial detection by detecting whether a person has a tendency to experience problems in his mental health with an expert system using the dempster-shafer method which is a method based on the theory of belief functions using the belief variable (belief) and plausibility variable. The results of this study are a web-based expert system that can detect whether a person has a tendency for mental health problems based on the conditions experienced by the user and provide information related to mental health. Testing the accuracy of the system comparation between system result and expert result used 100 data and get 94% percentage and system usability testing based on 31 correspondents and get score 3.95 out of 5. We hope that further research can develop the system by integrating the system with psychologists in around the user’s locations to consult so it is easier for users to provide more detailed solutions related to problems in mental health. In addition, it is expected that the system can be developed from the web platform to be based on Android / iOS that it will be easier for users to access the system.